Detection of Copy Number Variations from HIF1A and HIF2A Gene as Genetic Determinants of Bovine Carcass Traits - Enhui Jiang; Yingjie Zhou; Yunan He; Zhuoyuan He; Hongyang Wang; Leijing Zhu; Chuanying Pan; Chuzhao Lei; Fugui Jiang; Xianyong Lan (Agriculture)
The beef cattle industry has seen rapid expansion, necessitating the optimization of slaughter traits for enhanced economic benefits. Copy number variation (CNV) has emerged as a pivotal molecular marker in marker-assisted selection (MAS) for genetic improvement in livestock. In this study, we focused on CNVs within the HIF1A and HIF2A genes, which play crucial roles in hypoxic signaling and energy metabolism. Four CNVs were identified in the bovine HIF1A gene and three in HIF2A using the AAOD database. In Gaoqing Black cattle (GQB), the distribution of CNVs for both genes was investigated, revealing predominantly median copy numbers. Association analysis showed a significant relation between CNVs in HIF1A and carcass traits such as cervical vertebrae (CNV1), initial weight and beef diaphragm (CNV2), slaughter weight and chuck (CNV3), and femur and chuck (CNV4) (p < 0.05 or p < 0.01). Similarly, CNVs in HIF2A are associated with traits like beef diaphragm, beef knuckle bone, and beef tendon (CNV1), longissimus dorsi width and beef diaphragm (CNV2), and slaughter weight and limb weights (CNV3) (p < 0.05 or p < 0.01). These findings provide insights into the potential influence of CNVs in HIF1A and HIF2A on carcass traits in Gaoqing Black cattle, offering a theoretical basis for genetic improvement in beef cattle breeding.